Is progesterone the key regulatory factor behind ovulation rate in sheep? - Bartlewski, P. M.; Sohal, J.; Paravinja, V.; Baby, T.; Oliveira, M. E. F. [UNESP]; Murawski, M.; Schwarz, T.; Zieba, D. A.; Keisler, D. H. (Elsevier B.V., 2017)
Ovarian antral follicles in the ewe grow in an orderly succession, producing 3 to 4 waves per estrous cycle. In prolific sheep, some large antral follicles from the second-to-last wave of the estrous cycle are added to the ovulatory follicles emerging just before estrus to give a higher ovulation rate; it is feasible that regression of these follicles is prevented by an increase in serum concentrations of FSH or LH pulsatility at proestrus. Prolific sheep tend to have a shorter luteal phase than nonprolific ewes and there is a great deal of evidence that luteal progesterone (P-4), in addition to regulating LH release, may govern the secretion of FSH heralding the emergence of follicular waves. The specific purpose of this study was to determine whether or not extending the duration of the luteal phase in prolific sheep to that typically seen in nonprolific breeds would alter the follicle wave dynamics and ovulation rate. In 2 separate experiments, exogenous P-4 (7.5 mg per ewe intramuscularly) was administered on day 11 at PM and day 12 at AM (day 0 = first ovulation of the interovulatory interval studied) in moderately prolific Rideau Arcott x Polled Dorset ewes (experiment 1, n = 8) and highly prolific Olkuska ewes (experiment 2, n = 7; TRT), whereas the equinumerous groups of animals served as controls (CTR). Transrectal ovarian ultrasonography was performed daily, and jugular blood samples were drawn twice a day from day 9 until the next ovulation. Progesterone injections resulted in relatively uniform increments in serum P-4 levels, but the mean duration of the interovulatory interval did not differ (P > 0.05) between TRT and CTR groups of ewes in either experiment. The mean ovulation rate post-treatment was 1.6 +/- 0.2 vs 3.2 +/- 0.4 (experiment 1, P < 0.001) and 3.2 +/- 0.8 vs 4.0 +/- 1.0 (experiment 2, P > 0.05) in TRT vs CTR, respectively. The number and percentage of ovulating follicles from the penultimate wave of the interovulatory interval studied was 025 +/- 0.16 vs 1.75 +/- 0.45 (P < 0.01) and 25.0 +/- 16.4% vs 75.0 +/- 16.4% (P < 0.05) in experiment 1, and 0.50 +/- 0.30 vs 1.60 +/- 0.40 (P < 0.05) and 13.8 +/- 9.0% vs 53.4 +/- 16.7% (P < 0.05) in experiment 2, for TRT vs CTR, respectively. In summary, administration of P-4 at the end of diestrus decreased the incidence of ovulations from the penultimate wave of the estrous cycle in both the moderately and highly prolific strains of sheep, but it reduced the ovulation rate only in moderately prolific ewes. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Sheep; Ovulation rate; Progesterone; FSH; Ultrasonography